Performance evaluation of AlTiN coated carbide tools during machining of ceramic reinforced Cu-based hybrid composites under cryogenic, pure-minimum quantity lubrication and dry regimes. (September 2022) - Şap, Serhat; Usca, Üsame Ali; Uzun, Mahir; Kuntoğlu, Mustafa; Salur, Emin
In this study, the machining performance of 10 wt.% B-Ti-SiCp particles reinforced Cu-based hybrid composites were investigated under dry, minimum quantity lubrication (MQL) and cryogenic LN2 assisted environments during milling. In-depth analyses comprising of tool wear development, surface roughness, surface texture, cutting temperature, cutting energy, and chip morphologies were thoroughly performed. According to the experimental results, MQL environment was found to be most influential method to prevent build-up-edge formation. In addition, LN2 assisted cryogenic coolant medium is the most powerful method in all machining characteristics as providing better tribological properties. The paper proposes a novel approach for improved machinability performance of Cu-based hybrid composites with sustainable techniques.